Proceeedings of the Second European Workshop on Wireless Sensor Networks, 2005.
DOI: 10.1109/ewsn.2005.1462018
|View full text |Cite
|
Sign up to set email alerts
|

A biologically-inspired approach to designing wireless sensor networks

Abstract: Abstract--In this paper, we contend that there are significant advantages in treating some classes of sensor networks as biological-like systems-both in structural design characteristics and in operational processes. We show how this design process leads to a sensor network system that is robust to topological changes, is scaleable and self-organising-and has a number of other desirable features. The operating system kOS was designed to support the operation of distributed biologically-inspired algorithms, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Britton et al [20] proposes to apply biological mechanisms to an operating system for sensor networks, called kOS, in order to make them robust to topological changes, scalable and self-organizing. However, kOS has not implemented any specific biological mechanisms yet.…”
Section: Related Workmentioning
confidence: 99%
“…Britton et al [20] proposes to apply biological mechanisms to an operating system for sensor networks, called kOS, in order to make them robust to topological changes, scalable and self-organizing. However, kOS has not implemented any specific biological mechanisms yet.…”
Section: Related Workmentioning
confidence: 99%
“…The optimization can be accomplished even in the case that each individual is much limited in sensing ability. Recently, many works have been done on the biologically-inspired WSN modeling, such as cooperative routing [23], operating system design [24], thread management [25], time synchronicity [26] and sensor movement strategy [27]. However, little research has been reported on the biologically-inspired SWC.…”
Section: The Biologically-inspired Scheme For Sensor Wakeup Controlmentioning
confidence: 99%
“…Our first analytical model employs the known analogy between the information spread in a network of communicating agents and the propagation of epidemics across a population. Although the epidemiology-based approach has been applied to other problem domains [5], [6], [7], [8], [9], [10]), it has not been specifically used to study the effects of dynamic sensor activation. We extend the model initially proposed in [8].…”
Section: Introductionmentioning
confidence: 99%